Some Methods Used by Mathematics Teachers in Solving Equations - Baiduri Baiduri (Journal of Education and Learning (EduLearn), 2018)
This study aimed at analyzing and describing Various Methods used by mathematics teacher in solving equations. Type of this study is descriptive by subject of this study comprised 65 mathematics teachers in senior, junior, and primary schools respectively 15, 33, and 17 in numbers. The data were collected from the answer to containing four problems of equation. Data Coding was conducted by two coding personnel to obtain credible data. The data were then analyzed descriptively. It has been found that the teachers have implemented a method for solving equation problems by means of operation on one side of equation and procedural operation. This method has been dominantly used by the teachers to solve to the equation problems. The other method was doing operation on both sides of the equation simultaneously by focusing on similar elements on both sides of the equation.